Ownership Structure And Risk Taking Of Malaysian Commercial Banks: The Moderating Effects Of Capital Adequacy Ratio - Fauzias Mat Nor; Nasyra Ab. Jamil; Rasidah Mohd. Said (MCSER-Mediterranean Center of Social and Educational Research, 2024)
Non-Indexed Publication